PERILAKU HARGA DAN INTEGRASI PASAR HORIZONTAL BERAS DI PROPINSI BENGKULU - Suryana, Cahya; Asriani, Putri Suci; Badrudin, Redy (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2014)
Rice is one of the strategic foods in Indonesia. According to Alimoeso (2011), approximately 95% of the Indonesian people depend on rice, poor families allocate nearly 21.8% of its expenditure on rice. In addition, of rice consumption estimates is the highest Indonesian in Southeast Asia, namely, 139 kg / capita / year, of which about 120 kg consumed directly. That is why price policy is important instrument for improving the wealth of rice farmers as well as rice traders. The purpose of the study was to analyze the price behavior, (2) analyze market integration (3) to analyze market causality, and (4) determine the rice leader market in Bengkulu Province. This study used a method of analysis of price behavior, market integration, unit root test, cointegration test and analysis methods of Engle and Granger causality. The results rice price behavior in Bengkulu do not fluctuate indicating by lower value of show that coefficient variable. There is strong integration market in price formation between Bengkulu, Rejang Lebong, North Bengkulu and South Bengkulu markets. The causality test proved that the prices of the price of North Bengkulu affect the price rice Bengkulu City, Rejang Lebong and South Bengkulu, and none of the three areas that affect the price of rice in North Bengkulu, and the leader market is North Bengkulu